Sexual and reproductive health needs of people living with HIV/AIDS and the social responses in association with stigma and discrimination - Mallick, Subrata Kumar; Roy, Tuhin (Mediscope, 2020)
This cross-sectional study aimed at determining the sexual and reproductive health needs as well as to reveal the level and manifestation of stigma and discrimination associated with the daily lives of the people living with HIV/AIDS (PLWHA) at Khulna City Area in Bangladesh. The sample size was 20, which was selected purposively, and data were collected by the interviewers from August 2013 to December 2013. The findings of the study revealed that extra marital sexual relationships, partners’ infection and blood transmission played a dominant role as the medium of HIV infection. NGOs were the predominant source of getting health care facilities for the PLWHA and they had to wait for a month to receive STIs treatment and the counseling support, which increased their vulnerability towards AIDS. A number of respondents were eager to conceive and, in this case, treatment and counseling support before and after conception, proper nutrition support, prevention of mother to child transmission support and high cost medicine support were needed for them. The facts of stigma and discrimination, the restriction placed on their free movement, exclusion from social and religious functions, opportunities and participation on the social and economic processes had direct consequences on their daily lives. Therefore, IGA support, ensure quality treatment in the stigma free environment, and widespread awareness campaign regarding HIV/AIDS related issues were highly recommended by the PLWHA. Mediscope Vol. 7, No. 1: Jan 2020, Page 7-16